Scandium-doped spinel sulfide and preparation method and application thereof
The energy band structure of NiCo2S4 material is regulated through scandium doping technology, and the problem of insufficient activity and stability of non-precious metal OER catalysts is solved, efficient oxygen precipitation catalysis and long-term stability are achieved, and the efficiency of hydrogen production by electrolyzing water is improved.
Patent Information
- Application Number
- CN202310993937.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-08
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-08-08
AI Technical Summary
The existing non-precious metal OER catalysts exhibit poor activity and poor stability in oxygen evolution reactions, which limits the application of electrolytic water hydrogen production technology.
Through the rare earth element scandium doping technology, the energy band structure of NiCo2S4 material is regulated, its conductivity and reaction stability are improved, and a scandium-doped spinel-type sulfide catalyst is prepared.
It achieves efficient catalytic performance of oxygen precipitation and long-term stability, reduces the overpotential and improves the efficiency of hydrogen production by electrolyzing water.
Smart Images

Figure CN117263264B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of electrochemical catalysis, and in particular to a scandium-doped spinel sulfide and a preparation method and application thereof. Background Art
[0002] With the development of social economy, fossil fuel resources are becoming increasingly depleted, and environmental pollution problems are becoming increasingly serious. The development and utilization of clean renewable energy has become the only way to solve the energy crisis and environmental problems. As an ideal clean fuel, hydrogen has the advantages of abundant resources and pollution-free process, and has attracted much attention in recent years. However, the oxygen evolution reaction (OER) occurring at the anode during the electrolysis of water is slow and requires a relatively high overpotential, which limits the practical application of hydrogen production technology by electrolysis of water. The development of efficient OER electrocatalysts is of great significance to improving the efficiency of hydrogen production by electrolysis of water and reducing costs.
[0003] At present, precious metal oxides IrO2 and RuO2 are the most active OER catalysts, but their scarcity and high cost restrict their large-scale application. Non-precious metal OER catalysts, such as transition metal sulfides and hydroxides, have attracted widespread attention due to their abundance and low prices. However, due to their intrinsic structure and electrochemical properties, these materials often exhibit poor OER activity and unsatisfactory stability. Rare earth materials, due to their special outer electron configuration, can regulate and modify the structure of the crystal to optimize their electrocatalytic activity and stability.
[0004] Therefore, it is a technical challenge to synthesize a non-precious metal sulfide material with controllable electronic structure through rare earth doping technology, which can significantly enhance the OER performance and realize its efficient and stable catalytic effect. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a scandium-doped spinel sulfide. By doping with the rare earth element scandium (Sc), the energy band of the NiCo2S4 material is regulated by utilizing the special 3d4s electronic structure of scandium, which can significantly improve the conductivity of the material and help to improve its reaction stability, so that the spinel sulfide material of the present invention has excellent conductivity and a lower oxygen evolution reaction energy barrier.
[0006] In a first aspect, the present invention provides a scandium-doped spinel sulfide, the composition of which comprises scandium-doped NiCo2S4. In the present invention, NiCo2S4 has a spinel structure.
[0007] In some embodiments, based on 100% NiCo2S4, the molar content of scandium doping is 5%-30%.
[0008] In some embodiments, based on 100% NiCo2S4, the molar content of scandium doping is 5%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, or 30%.
[0009] In some embodiments, in the sulfide, the element molar ratio of Sc to Ni is (0.05-0.3):1, for example, 0.1:1, 0.12:1, 0.15:1, 0.18:1, 0.20:1, 0.22:1, 0.25:1, or 0.30:1.
[0010] In some embodiments, in the sulfide, the element molar ratio of Sc to Ni is (0.1-0.2):1.
[0011] In some embodiments, the molar ratio of the elements in the sulfide is: Sc:Ni:Co=(0.1-0.2):1:2.
[0012] In a second aspect, the present invention provides a method for preparing a scandium-doped spinel sulfide, which comprises the following steps:
[0013] 1) preparing a Sc-doped Ni-Co hydroxide precursor;
[0014] 2) sintering the precursor to obtain Sc-doped NiCo2O4;
[0015] 3) Sulfiding the Sc-doped NiCo2O4.
[0016] In some embodiments, the preparation of the Sc-doped Ni-Co hydroxide precursor is carried out by heating an aqueous solution of a scandium source, a nickel source and a cobalt source at 100-150°C (e.g., 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, or 150°C) for a reaction preferably for 10-15h, more preferably for 10-12h.
[0017] In some embodiments, the Sc-doped Ni-Co hydroxide precursor is prepared by reacting aqueous solutions of a scandium source, a nickel source and a cobalt source at 110-130° C., preferably 115-125° C., for 10-15 hours, more preferably 10-12 hours.
[0018] In some embodiments, the preparation of the Sc-doped Ni—Co hydroxide precursor further comprises adding a chelating agent, preferably urea.
[0019] In some embodiments, the molar ratio of the scandium source to the nickel source is (0.05-0.3):1, for example 0.1:1, 0.12:1, 0.15:1, 0.18:1, 0.20:1, 0.22:1, 0.25:1, or 0.30:1.
[0020] In some embodiments, the molar ratio of the scandium source to the nickel source is (0.1-0.2):1.
[0021] In some embodiments, the molar ratio of the scandium source, the nickel source and the cobalt source is (0.05-0.3):1:2; preferably, the molar ratio of the scandium source, the nickel source and the cobalt source is (0.1-0.2):1:2.
[0022] In some embodiments, the scandium source is selected from scandium nitrate and / or scandium chloride, preferably scandium nitrate.
[0023] In some embodiments, the nickel source is selected from nickel nitrate and / or nickel chloride, preferably nickel nitrate.
[0024] In some embodiments, the cobalt source is selected from cobalt nitrate and / or cobalt chloride, preferably cobalt nitrate.
[0025] In some embodiments, in the preparation method, a scandium source, a nickel source, and an aqueous solution of a cobalt source are placed in a hydrothermal kettle, hydrothermally heated to 120° C., and maintained for 12 hours to obtain a Sc-doped Ni—Co hydroxide precursor.
[0026] In some embodiments, the sintering is performed by heating the Sc-doped Ni-Co hydroxide precursor at 300-400° C. (e.g., 300° C., 320° C., 350° C., 380° C., 400° C., or 420° C.) for 3-6 h (e.g., 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h). In some embodiments, the sintering is performed in a muffle furnace.
[0027] In some embodiments, the sintered Sc-doped NiCo2O4 is washed with a solvent; in some embodiments, the solvent is water and ethanol. In some embodiments, after washing, the Sc-doped NiCo2O4 is dried.
[0028] In some embodiments, the sulfurization is performed by chemical vapor deposition.
[0029] In some embodiments, the sulfurization is carried out by heating the Sc-doped NiCo2O4 in an inert atmosphere in the presence of a sulfur source; preferably, heating at 100°C-600°C (e.g., 150°C, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C), preferably 350-400°C, for example 380°C, and the preferred heating time is 1-8h, preferably 4-6h.
[0030] In some embodiments, the sulfur source comprises sulfur powder or thiourea, preferably sulfur powder. In some embodiments, during the vulcanization, the heating is heated to 100-600°C (e.g., 150°C, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C) at a rate of 10-15°C / min and maintained for 1-8h, preferably 4-6h.
[0031] In some embodiments, the inert gas may be selected from nitrogen and argon, preferably nitrogen.
[0032] In some embodiments, the method for preparing the scandium-doped spinel sulfide comprises the following specific steps:
[0033] Step S1: adding the solutions of scandium source, nickel source and cobalt source into a hydrothermal reactor and reacting at a high temperature of 110-130° C. for 10-15 hours;
[0034] Step S2: centrifuge the product obtained in step S1, wash with water and ethanol, and dry in an oven at 50-70°C;
[0035] Step S3: placing the precursor obtained in step S2 into a muffle furnace for high temperature oxidation at 300°C for 3-6 hours;
[0036] Step S4: placing the oxide treated in step S3 in a tube furnace, adding sublimated sulfur, and reacting with high-temperature inert gas to obtain the scandium-doped spinel sulfide catalyst.
[0037] In a third aspect, the present invention provides an OER catalyst, which contains the sulfide described in the present invention or the sulfide prepared by the preparation method described in the present invention.
[0038] In some embodiments, the catalyst further comprises a substrate, and the scandium-doped NiCo2S4 (hereinafter referred to as Sc-NiCo2S4) is loaded on the substrate. In some embodiments, the substrate is a conductive substrate. In some embodiments, the substrate is selected from carbon cloth.
[0039] In some embodiments, the loading amount of Sc-NiCo2S4 on the substrate is 2-10 mg / cm 2 .
[0040] In some embodiments, the OER catalyst is prepared by mixing and grinding the sulfide described in the present invention or the sulfide prepared by the preparation method described in the present invention with PVDF and N-methylpyrrolidone, and then coating the mixture on a carbon cloth.
[0041] In some embodiments, the molar ratio of the catalyst of the present invention or the catalyst prepared by the preparation method of the present invention to PVDF and N-methylpyrrolidone is 10:2:5. Before attaching the sulfide of the present invention to the substrate, the surface of the substrate can be washed with an acid solution, such as ultrasonic washing, and then washed with an organic solvent and water and dried. In some embodiments, the acid solution can be an organic acid solution or an inorganic acid solution, preferably at least one of formic acid, acetic acid, sulfuric acid, and nitric acid. In some embodiments, the concentration of the acid solution is 0.5M (mol / L)-1.5M, preferably 0.8M-1.2M.
[0042] In a fourth aspect, the present invention provides the use of the sulfide described in the present invention, or the sulfide prepared by the preparation method described in the present invention, or the OER catalyst described in the present invention in anode catalysis of water decomposition.
[0043] In a fifth aspect, the present invention provides a method for water electrolysis, using the sulfide described in the present invention or the sulfide prepared by the preparation method described in the present invention or the OER catalyst described in the present invention to catalyze the electrolysis of water.
[0044] Beneficial Effects
[0045] The present invention provides a scandium-doped NiCo2S4 material, which is a rare earth-doped high-activity oxygen evolution catalyst. It has good conductivity, a large surface area and a large number of active sites, so that the present invention has good oxygen evolution catalytic performance at 10 mA cm -2 The lower overpotential is only 231.3mV.
[0046] In addition, the oxygen evolution catalyst of the present invention has good stability and can be stable for at least 20 hours.
[0047] Terminology
[0048] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0049] In the following, all numbers disclosed herein are approximate, regardless of whether the word "about" or "approximately" is used. The value of each number may vary by 1%, 2%, 5%, 7%, 8%, 10%, 15% or 20%. Whenever a number with a value of N is disclosed, any number with a value of N+ / -1%, N+ / -2%, N+ / -3%, N+ / -5%, N+ / -7%, N+ / -8%, N+ / -10%, N+ / -15% or N+ / -20% will be explicitly disclosed, where "+ / -" means plus or minus. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention, but do not constitute a limitation of the present invention.
[0051] Figure 1 This is the X-ray diffraction pattern of Sc-NiCo2S4 prepared in Example 1.
[0052] Figure 2 This is the EDS graph of Sc-NiCo2S4 prepared in Example 1.
[0053] Figure 3 The linear sweep voltammetry curves of the products prepared in Examples 1-3 and Comparative Example as catalysts for oxygen evolution reaction.
[0054] Figure 4 This is the stability curve of the oxygen evolution reaction of the product obtained in Example 1.
[0055] Figure 5 The in-situ electrocatalytic Raman spectra of the products prepared in Example 1 and the comparative example.
[0056] Figure 6 The in-situ electrocatalytic infrared spectra of the products prepared in Examples 1-3 and Comparative Example are shown. DETAILED DESCRIPTION
[0057] In order to enable those skilled in the art to better understand the technical solution of the present invention, some non-limiting embodiments are further disclosed below to further describe the present invention in detail.
[0058] The reagents used in the present invention can be purchased from the market or prepared by the method described in the present invention.
[0059] Ultrapure water with a conductivity of 18.25 MΩ was used in the experiment, and all reagents used in the experiment were of analytical grade.
[0060] Main instruments and reagents used:
[0061] CHI760E electrochemical workstation (Shanghai Chenhua Instrument Co., Ltd.) was used for linear sweep voltammetry test;
[0062] UPT laboratory ultrapure water device (Chengdu Ultrapure Technology Co., Ltd.), used to prepare ultrapure water;
[0063] A desktop X-ray diffractometer (Rigaku Corporation, MiniFlex600) was used for X-ray diffraction characterization;
[0064] Fourier transform infrared spectrometer (BRUKER TENSOR 27) for characterization of oxygen evolution catalysts;
[0065] Laser confocal Raman spectrometer (HORIBA FRANCE SAS, Lab RAM HR Evolution) was used for the characterization of oxygen evolution catalysts;
[0066] Electronic balance (Shanghai Bo Le Mechanical and Electrical Equipment Co., Ltd.), used for weighing drugs;
[0067] Vacuum drying oven (Shanghai Yiheng Scientific Instrument Co., Ltd.);
[0068] KQ5200 ultrasonic cleaner (Kunshan Ultrasonic Instrument Co., Ltd.);
[0069] Box furnace (Hefei Kejing Material Technology Co., Ltd.);
[0070] High temperature tube furnace (Hefei Kejing Material Technology Co., Ltd.);
[0071] Three-electrode system (Wuhan Gaoshi Ruilian Technology Co., Ltd.): reference electrode Hg / HgO, Pt electrode and auxiliary electrode Pt sheet;
[0072] Desktop drying oven (Chongqing Testing Equipment Factory);
[0073] Nickel nitrate (Chengdu Kelong Chemical Co., Ltd.);
[0074] Cobalt nitrate (Chengdu Kelong Chemical Co., Ltd.);
[0075] Scandium nitrate (Chengdu Kelong Chemical Co., Ltd.);
[0076] Urea (Chengdu Kelong Chemical Co., Ltd.);
[0077] Ethanol (Tianjin Fuyu Fine Chemical Co., Ltd.);
[0078] Carbon cloth (Shanghai Hesen Electric Co., Ltd.).
[0079] Preparation of spinel sulfide catalyst:
[0080] Example 1
[0081] Dissolve 1.33mmol of Ni(NO3)2·6H2O, 2.67mmol of Co(NO3)2·6H2O, 0.133mmol of Sc(NO3)2·6H2O and 0.5g of urea in 40ml of deionized water and stir at room temperature until completely dissolved. Transfer the resulting solution to a 100ml hydrothermal reactor and react at 120°C for 12h. After the reactor temperature naturally drops to room temperature, wash the resulting product with water and ethanol, centrifuge (6000r / min, 3min) 3 times, and then dry it in a vacuum drying oven overnight to obtain a Sc-doped Ni-Co hydroxide precursor.
[0082] The precursor was placed in a box furnace and fired at 300°C for 3h to obtain Sc-doped NiCo2O4. 300mg of sulfur powder and 20mg of oxide powder were placed in two magnetic boats, spread evenly, and then the magnetic boats were placed in a tube furnace 20cm apart. After evacuation, the mixture was heated to 380°C at a rate of 10°C / min in a N2 atmosphere and maintained for 6h. Finally, the system was cooled in a nitrogen atmosphere to obtain Sc-doped NiCo2S4.
[0083] According to the ratio of scandium content to nickel content, the feed ratio of Sc to Ni is 1:10.
[0084] The XRD pattern of the final product obtained in this example is as follows Figure 1 As shown in FIG. 1 , the characteristic peaks of the embodiment are clearly visible at 2θ=31.47°, 38.17°, 50.25° and 55.0°, and the positions of these peaks are very close to the diffraction angles of the (311), (400), (511) and (440) crystal planes (PDF#20-0782) of the standard NiCo2S4, indicating that NiCo2S4 was successfully prepared. Its EDS spectrum is shown in FIG. Figure 2 As shown, it indicates that Sc is successfully doped into NiCo2S4.
[0085] Example 2
[0086] Dissolve 1.33mmol Ni(NO3)2·6H2O, 2.67mmol Co(NO3)2·6H2O, 0.267mmol Sc and 0.5g urea in 40ml deionized water and stir at room temperature until completely dissolved. Transfer the resulting solution to a 100ml hydrothermal reactor and react at 120°C for 12h. After the reactor temperature naturally drops to room temperature, wash the resulting product with water and ethanol, centrifuge (6000r / min, 3min) 3 times, and then dry it in a vacuum drying oven overnight to obtain a Sc-doped Ni-Co hydroxide precursor.
[0087] The precursor was placed in a box furnace and fired at 300°C for 3h to obtain Sc-doped NiCo2O4. 300mg of sulfur powder and 20mg of oxide powder were placed in two magnetic boats, spread evenly, and then the magnetic boats were placed in a tube furnace 20cm apart. After evacuation, the mixture was heated to 380°C at a rate of 10°C / min in a N2 atmosphere and maintained for 6h. Finally, the system was cooled in a nitrogen atmosphere to obtain Sc-doped NiCo2S4.
[0088] According to the ratio of scandium content to nickel content, the feed ratio of Sc to Ni is 2:10.
[0089] Example 3
[0090] Dissolve 1.33mmol of Ni(NO3)2·6H2O, 2.67mmol of Co(NO3)2·6H2O, 0.400mmol of Sc and 0.5g of urea in 40ml of deionized water and stir at room temperature until completely dissolved. Transfer the resulting solution to a 100ml hydrothermal reactor and react at 120°C for 12h. After the reactor temperature naturally drops to room temperature, wash the resulting product with water and ethanol, centrifuge (6000r / min, 3min) 3 times, and then dry it in a vacuum drying oven overnight to obtain a Sc-doped Ni-Co hydroxide precursor.
[0091] The precursor was placed in a box furnace and fired at 300°C for 3h to obtain Sc-doped NiCo2O4. 300mg of sulfur powder and 20mg of oxide powder were placed in two magnetic boats, spread evenly, and then the magnetic boats were placed in a tube furnace 20cm apart. After evacuation, the mixture was heated to 380°C at a rate of 10°C / min in a N2 atmosphere and maintained for 6h. Finally, the system was cooled in a nitrogen atmosphere to obtain Sc-doped NiCo2S4.
[0092] According to the ratio of scandium content to nickel content, the feed ratio of Sc to Ni is 3:10.
[0093] Comparative Example
[0094] Dissolve 1.33mmol of Ni(NO3)2·6H2O, 2.67mmol of Co(NO3)2·6H2O and 0.5g of urea in 40ml of deionized water and stir at room temperature until completely dissolved. Transfer the resulting solution to a 100ml hydrothermal reactor and react at 120°C for 12h. After the reactor temperature naturally drops to room temperature, wash the resulting product with water and ethanol, centrifuge (6000r / min, 3min) 3 times, and then dry it in a vacuum drying oven overnight to obtain a Ni-Co hydroxide precursor.
[0095] The precursor was placed in a box furnace and fired at 300°C for 3h to obtain NiCo2O4. 300mg of sulfur powder and 20mg of oxide powder were placed in two magnetic boats, spread evenly, and then the magnetic boats were placed in a tube furnace 20cm apart. After evacuation, the system was heated to 380°C at a rate of 10°C / min in a N2 atmosphere and maintained for 6h. Finally, the system was cooled in a nitrogen atmosphere to obtain NiCo2S4.
[0096] Test example:
[0097] 1. Hydrophilic carbon cloth treatment:
[0098] Cut a piece of carbon cloth (CC) into (2cm×3cm) specifications, rinse with distilled water and clean in ultrasound for 15 minutes to clean the dust and impurities on the surface of the base carbon cloth. Then put the carbon cloth into nitric acid solution. After the reddish brown gas (NO2) dissipates, take out the carbon cloth, put it into deionized water and ethanol for ultrasound for 15 minutes respectively, repeat 2-3 times, and finally store the carbon cloth in ethanol for later use.
[0099] 2. Preparation of OER catalytic materials:
[0100] The products obtained in Example 1 (Sc-NiCo2S4), Example 2, Example 3 and the comparative example were respectively mixed with PVDF and N-methylpyrrolidone in a ratio of 10:2:5, fully ground, scraped onto the above-mentioned carbon cloth, and then dried in a vacuum oven at 60°C for 2h to obtain OER catalytic materials.
[0101] 3. Test:
[0102] 3.1 Oxygen evolution reaction
[0103] The OER catalytic material was cut into 0.5 cm × 1 cm pieces and clamped on an electrode clamp as a working electrode, platinum was used as a counter electrode, and Hg / HgO was used as a reference electrode to form a three-electrode system. The three-electrode system was inserted into a 1 M potassium hydroxide solution with a molar concentration of 1.5 Å to carry out oxygen evolution reaction. The potential window was scanned in the range of 0.9 V to 1.9 V at a scanning rate of 2 mV / s to obtain an oxygen evolution curve, as shown in FIG. Figure 3 As shown. Figure 3 It can be seen that after Sc doping, the catalytic properties of NiCo2S4 are improved, especially the one with scandium doping concentration of 10-20 mol% (Example 1) has the best properties.
[0104] 3.2 Stability test
[0105] The OER catalytic material corresponding to Example 1 was cut into 0.5 cm × 1 cm pieces and clamped on an electrode clamp as a working electrode, platinum as a counter electrode, and Hg / HgO as a reference electrode to form a three-electrode system. The three-electrode system was inserted into a 1 M potassium hydroxide solution with a molar concentration of 2.5 Å to perform a constant current method stability test curve. Figure 4 It can be seen that in the current window of 10mV / cm 2 At a potential of , Example 1 has stability for more than 20 hours.
[0106] 3.3 Pre-oxidation efficiency
[0107] The in-situ Raman spectra corresponding to Example 1 and the comparative example are as follows: Figure 5 As shown, it can be seen that after scandium doping, the *OOH active site peak appears earlier and stronger, indicating that scandium doping improves the pre-oxidation efficiency.
[0108] The in-situ infrared spectra corresponding to Examples 1-3 and Comparative Examples are as follows Figure 6 As shown, scandium doping increases the peak intensity of active intermediate species, and also indicates that Sc doping is beneficial to regulating the electronic structure of the material and improving the pre-oxidation efficiency, thus helping to improve its electrocatalytic activity and stability.
[0109] The method of the present invention has been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein within the content, spirit and scope of the present invention to implement and apply the technology of the present invention. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters. It is particularly important to point out that all similar replacements and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention.
Claims
1. An OER catalyst comprising a scandium-doped spinel sulfide, the composition of which comprises Sc-doped NiCo2S4; In the sulfide, the element molar ratio of Sc to Ni is (0.1-0.2):1; The method for preparing the scandium-doped spinel sulfide comprises the following steps: 1) Preparation of Sc-doped Ni-Co hydroxide precursor; 2) sintering the precursor to obtain Sc-doped NiCo2O4; 3) Sulfiding Sc-doped NiCo2O4; The Sc-doped Ni-Co hydroxide precursor is prepared by heating an aqueous solution of a scandium source, a nickel source and a cobalt source at 115-125° C. for a reaction of 10-12 h; The preparation of the Sc-doped Ni-Co hydroxide precursor further comprises adding a chelating agent, wherein the chelating agent is urea; The molar ratio of the scandium source, the nickel source and the cobalt source is (0.1-0.2):1:2; The scandium source is selected from scandium nitrate, the nickel source is selected from nickel nitrate, and the cobalt source is selected from cobalt nitrate; The sintering is to heat the Sc-doped Ni-Co hydroxide precursor at 300-400 °C for 3-6 h; The sulfurization is achieved by chemical vapor deposition; the sulfurization is carried out by heating the Sc-doped NiCo2O4 to 350-400 °C at a rate of 10-15 °C / min in the presence of a sulfur source, and the heating time is 4-6 h; The sulfur source includes sulfur powder.
2. The OER catalyst according to claim 1, characterized in that The sintering is performed by heating the Sc-doped Ni-Co hydroxide precursor at 300-350 °C.
3. The OER catalyst according to claim 1, characterized in that The sulfidation is carried out by heating the Sc-doped NiCo2O4 in an inert atmosphere in the presence of a sulfur source.
4. The OER catalyst according to claim 1, characterized in that Also included is a substrate on which the sulfide is supported.
5. The OER catalyst according to claim 4, characterized in that The substrate is a conductive substrate.
6. The OER catalyst according to claim 4, characterized in that The substrate is carbon cloth.
7. The OER catalyst according to claim 4, characterized in that The loading amount of the sulfide on the substrate is 2 mg / cm 2 -10 mg / cm 2 .
8. Use of the OER catalyst according to any one of claims 1 to 7 in water decomposition anode catalysis.
9. A water electrolysis method, comprising catalytically electrolyzing water using the OER catalyst described in any one of claims 1 to 7.